Call for the Return to the Qualities of the Traditional Muslim Mind - Mohd Abbas Abdul Razak; Sayed Sikandar Shah Hanif; Muhammad Abdurrahman (Dinamika Ilmu, 2021)
The world we live today has undergone a dramatic change in values, science and technology. In a world so divided with contending ideologies and worldviews, humanity as a whole has derailed from its philosophy of co-existence, tolerance and mutual respect for one another’s faith and culture. The war that should have ended with the formation of the United Nations is still raging in many parts of the world. News and business are controlled by some powerful conglomerates. The gap between the haves and have not’s still persists. In the wake of the present global condition, Muslims and their religion are targeted and falsely labeled as a global threat. This apparent situation of the world calls for the new generation of Muslims to think and re-evaluate on how to respond to the challenges and criticisms that come from others. Moreover, they have to carve out new ways to co-exist with others and on how to preserve their religion and cultural heritage of the past. Through this paper, the researchers intend to investigate the style of thinking of the great Muslim scholars during the heydays of the Islamic civilization and propose the importance of reviving such an orientation of thinking in the contemporary Muslim world. As a qualitative study, the researchers intend to present some historical evidence on the remarkable achievement of the Muslim scholars of the bygone centuries. The textual and document analysis methods will be employed in interpreting the relevant data of the study. Pertinent data related to the research will be retrieved from print and electronic media.